94.5k views
1 vote
5x + 2y = 19 -x + 2y = 1

User Ibrahima
by
5.3k points

1 Answer

0 votes

The given expressions are,


\begin{gathered} 5x+2y=19\ldots\text{.}\mathrm{}(1) \\ -x+2y=1\ldots\text{.}\mathrm{}(2) \end{gathered}

From the second equation, we have,


x=2y-1\ldots\text{.}\mathrm{}(3)

Substituting this value in the first equation, we have,


\begin{gathered} 5(2y-1)+2y=19 \\ 10y-5+2y=19 \\ 12y=19+5 \\ 12y=24 \\ y=(24)/(12)=2 \end{gathered}

Now, substituting this value of y in equation 3, we have,


x=2*2-1=4-1=3

Thus, the solution is x = 3 and y = 2

User Justin Balvanz
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.